The behavior of Particulate Matter (PM10) Concentrations at Industrial Sites in Malaysia - Raffee, Ahmad Fauzi (International Journal of Integrated Engineering, 2019)
Particulate Matter (PM10) is one of the atmospheric pollutants that can cause significant effect to human health. Meteorological factors such as wind speed (WS), relative humidity (RH) and temperature (T), and gaseous pollutants namely surface layer ozone (O3), nitrogen dioxide (NO2), sulphur dioxide (SO2) and carbon monoxide (CO) are reported as some of the main factors that influence the concentration of PM10. Therefore, the aim of this study is to investigate the pattern and behaviour of PM10 concentration at three industrial sites which were Pasir Gudang in Johor, Perai in Penang and Nilai in Negeri Sembilan. In the current study, the descriptive statistics, correlation analysis and multiple linear regressions were used to analyse the hourly average data from 2010 to 2014. The maximum values of PM10 concentration recorded at Pasir Gudang, Nilai and Perai stations were 995 μg/m³, 711 μg/m³ and 232 μg/m³, respectively. Positive correlation was found between PM10 concentration and all gaseous pollutants. While for meteorological parameters, only wind speed had negative relations at all monitoring stations. The values of R2 for Pasir Gudang, Perai and Nilai were 0.539, 0.628 and 0.634, respectively. Overall, this study proved that most of the selected meteorological parameters and gaseous pollutants positively influenced the concentration of PM10.